การระบุยีนที่สามารถจับกับโปรตีนอี 7 เอชพีวีไทป์ 16 ที่เกี่ยวข้องกับการเกิดโพรโมเตอร์เมทิลเลชันในเซลล์ไลน์ C33A - จุฑามาศ สุขพัฒน์ธี (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
E7 protein generated by Human papillomavirus (HPV) type 16 is the main cause of cervical cancer. The previous report showed that E7 protein interacted with DNA methyltransferase 1 (Dnmt1) and bound with CCNA1 promoter inducing CCNA1 methylation and decreasing expression of gene. The purposes of this research are to identify genes that E7 can drive the promoter methylation and to prove the mechanism by which E7 induce promoter methylation. Aaccording to assume that when E7 protein interacts with transcription factor, It can bind to the gene promoter and induce methylation. To identify genes which were induced promoter methylation by HPV type 16, two techniques were used. First, Chromatin immunoprecipitation with DNA sequencing (ChIP-Seq) analysis was done by transfecting E7 recombinant plasmid into C33A cervical cancer cell line. After that, DNA fragments which can interact with E7 protein were precipitated and performed sequencing. Here, 3 genes consisting of  FAM189A1, ASAH2B, and RAPGEF4 were explored. Another technique was bioinformatics used for selecting genes in human genome database contain the same cis elememt as CCNA1 that is the binding site of transcription factor AP2 and YY1. The result showed 9 genes that could interact with AP2 and YY1 which were NOP56, MAG, FUS, EIF2S2, RPL7, RPL10, NINJ1, LGALS1 and CLDN5 gene. Here, FAM189A1 and NOP56 gene were selected for validation. Reverse transcription polymerase chain reaction was done in E7 and empty vector in transfected C33A and HEK293 cell line. The result show that the expression of  FAM189A1 and NOP56 gene was decreased in E7 transfected cell line. Moreover, methylation specific PCR were tested in HEK293 cell line to prove methylation of genes and the result showed that the methylation of FAM189A1 and NOP56 gene was increased in E7 transfected cell line.  ChIP–PCR was done for proving the binding of E7, AP2 and YY1 at the promoter of candidate genes. Both FAM189A1 and NOP56 gene were interacted with E7, AP2 and YY1. Taken together,  it was confirmed that the complex of  E7, AP2 and YY1 could induce FAM189A1 and NOP56 promoter methylation via interacted with gene promoters and suppressed genes expression leading to decrease the expression of FAM189A1 and NOP56 gene.